2016
DOI: 10.1590/1806-9282.62.08.774
|View full text |Cite
|
Sign up to set email alerts
|

Worse prognosis in breast cancer patients can be predicted by immunohistochemical analysis of positive MMP-2 and negative estrogen and progesterone receptors

Abstract: Introduction: Breast cancer is the most cause of death, and approximately 90% of these deaths are due to metastases. Matrix metalloproteinase-2 (MMP-2) gelatinase activity is able to degrade a major constituent of the tumor microenvironment, type IV collagen. Two well-established proteins used as markers in clinical practice for breast cancer are the receptors for estrogen (ER) and progesterone (PR). Although the presence of these receptors has been associated with a better prognosis, loss of these proteins ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Estrogen is a major driver of breast tumor cell growth (35) and ERα + breast cancer is the leading cause of breast cancer-associated mortality (36). ER and PR, along with matrix metalloproteinase-2, have a prognostic value in patients with breast cancer (37). Indeed, the ER and PR status of human breast cancer represent important prognostic and predictive markers for human breast cancer (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen is a major driver of breast tumor cell growth (35) and ERα + breast cancer is the leading cause of breast cancer-associated mortality (36). ER and PR, along with matrix metalloproteinase-2, have a prognostic value in patients with breast cancer (37). Indeed, the ER and PR status of human breast cancer represent important prognostic and predictive markers for human breast cancer (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The MMPs are involved in the key ECM degradation of proteolytic enzyme family (Curran et al 2004;Chen KE et al 2018;Qiao et al 2018) and are used to disrupt the interaction of cells-cells and cells-ECM by tissue remodelling. Studies have shown that the MMPs, particularly MMP-2 and MMP-9, key members of the MMP family, play a vital role in angiogenesis, invasion and transferring of tumours, including RCC (Ramos et al 2016;Chen et al 2017;Beardo et al 2019). Therefore, gelatine zymography was performed to determine the activity of MMP-2/-9.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 levels in circulating blood have been considered as a breast cancer metastasis marker and are related to mortality rates (19,20). 90% of patients that had worse prognoses (metastases and mortality), in a Brazilian cohort, had positive staining for MMP-2 in their breast cancer tumors (21), indicating they were in a "high-risk group". Clinical and preclinical studies have demonstrated MMP-2 involvement in several human cancers, including prostate, gastric, and pancreatic cancers.…”
Section: Role Of Evps Cargo As Potential Mechanisms For the Beneficia...mentioning
confidence: 99%